FAKTOR RISIKO KEJADIAN STUNTING PADA ANAK USIA 6-24 BULAN DI DAERAH NELAYAN (Studi Case-Control di Kampung Tambak Lorok, Kecamatan Tanjung Mas, Kota Semarang - Isninda Priska Syabandini; Siti Fatimah Pradigdo; Suyatno Suyatno; Dina Rahayuning Pangestuti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Stunting is the indicator of chronic malnutrition. Prevalence of stunting in Indonesia is high (>30%). Fishermen in Semarang City mostly located in North Semarang (70%) which in that area, there is a fishing village called Kampung Tambak Lorok. Prevalence of stunting in Tambak Lorok is medium (11,1%). The aim of this study was to analyze risk factors for the incidence of stunting among children under two years old in fisheries village. The type of this study was observational with case-control design. Samples were 30 cases and 30 controls selected using quota sampling. Samples were obtained through interview of questionnaire and recall 24 hours for two non-consecutive days. Data were analyzed to know p value, odds ratio, and convidence interval. This study found that risk factors of stunting among children aged 6 – 24 months were low birth weight (OR = 19,33; CI95%: 2,313-161,565; p= 0,01), history of infection (OR = 9, CI95%: 2,239-36,171; p=0,001), and low protein adequate level (OR= 4; CI9%: 1,27-12,6; p= 0,015). Risk factors that were not influenced the incidence of stunting among children 6 – 24 months were low maternal education level, low maternal knowledge, low family income, inadequate nutritional caring pattern, non-exclusive breastfeeding practice, low energy adequate level, This study suggest that public health center and public health officer to monitor pregnant women health status until their children reach two years old regularly. Hence, the increasing of stunting incidence can be prevented